Analisi IQ dan EQ Terhadap Prestasi Belajar PJOK Pada Peserta Didik Kelas VI di Inclusive School Culture - Aditria, Intan Ayu Putri; Priambodo, Anung; Arief, Nur Ahmad (Ilmu Olahraga, 2025)
This study aims to analyze the relationship between intellectual intelligence (IQ) and emotional intelligence (EQ) on physical education (PJOK) learning achievement in sixth grade students at SDN Wonorejo V/316 Surabaya, which implements an inclusive school culture. This study uses a quantitative correlational approach with an ex post facto design. The research subjects were 30 students who were selected purposively. Data were collected through IQ tests, EQ questionnaires, documentation of PJOK scores, and interviews with six students representing high and low IQ categories. The data analysis techniques used were Pearson correlation test and multiple linear regression. The results showed that there was a very strong relationship between IQ and PJOK learning achievement (r = 0.965; sig = 0.000), and a significant relationship between EQ and learning achievement (r = 0.476; sig = 0.008). Simultaneously, IQ and EQ contributed 93.1% to students' PJOK learning achievement (R² = 0.931). Interviews showed that an inclusive environment plays a role in shaping students' social interactions, empathy, and cooperative attitudes, which also support successful PJOK learning.